Social Construction of Caesarean Section Among Women in Nandom Municipality in the Upper West Region of Ghana - Kuuwiedome, J. (University of Ghana, 2025)
Caesarean section remains a life-saving obstetric intervention that can effectively be prioritized to deliver expectant mothers when spontaneous vaginal delivery is not feasible due to medical or labour-related challenges to prevent maternal and neonatal mortality. Despite this, women are unwilling to take up CS as an alternative childbirth method when the need arises in labour but are much concerned about the views of their significant others at the expense of saving their lives and that of their unborn babies. However, there is paucity of literature on how the women construct CS in Ghana. This study therefore focused on assessing the social construction of CS among women in Nandom Municipality, Ghana. An exploratory, descriptive design with qualitative approach was employed in this study. Sixteen (16) women who have never undergone CS delivery were purposely selected from St. Theresa’s hospital to participate in the study. Face - to -face interview was conducted using a semi-structured interview guide to collect the data from the participants. Thematic content Analysis (TCA) was used to analyse data that was audio taped and transcribed verbatim. Seven (7) themes and twenty-two (22) subthemes were identified from the data. Three (3) main themes were obtained based on the theory of social construction and four (4) additional themes emerged from the data. The findings established that women have their own different subjective meanings about CS based on their understanding as well as varied beliefs, and perceptions that have influence on their decision to choose CS as a birth method in times of need. These findings suggest that several factors influence women’s willingness to uptake CS as an alternative childbirth strategy when medically indicated to save their lives and that of their babies. Therefore, there is the need for the development of health education and communication strategies aimed at promoting women's understanding and their willingness to accept CS when the need arises as an alternative childbirth method to normal vaginal delivery. The findings of this study have implications for nursing and midwifery practice, nursing and midwifery research and policy formulation.
MPhil. Midwifery
Keywords: Caesarean section; mothers; vaginal delivery; Nandom Municipality; Ghana